The influence of safety knowledge, safety leadership, and safety motivation towards safety behavior among offshore oil and gas employees - Ching, Sea Lee (2017)
Safety behavior is vital in reducing injuries and accident in the workplace by identifying the workplace hazard, and to combat them to the minimal accident rate. It has positive influence on both employees and employers behavior towards safety and health. This study explored the relationship between safety knowledge, safety leadership, and safety motivation towards safety behavior among offshore oil and gas workers in Terengganu. The information was collected by questionnaire distribution to offshore oil and gas workers and the total numbers of workers responded was 170 out of 300. The finding of this study revealed that safety leadership with respect to safety policy is positively significant with safety behavior. Besides, safety motivation is proven that it has positive significant relationship with safety behavior. Besides, the relationship between safety knowledge and safety compliance has a positively significant relationship between these two variables. Lastly, the results obtained from this study also revealed that there is a positively significant relationship between safety leadership with respect to safety motivation with safety participation. The findings give an insightful information and guidance for researchers and practitioners to identify solutions that can help to improve safety and health at workplace.